I. 3x + 5 - 4x - 10x = -17 + 3x - 7 + 3x
-11x + 5 = -24 + 6x
29 = 17x
II. -2x - 1 - 4x + 12 = -4x = 3 + 12x + 1
-6x + 11 = 8x + 4
7 = 14x
III. -9x - 3 + 5x + 17 = -5 + 3x - 2 - 8x + 1
-4x + 14 = -6 - 5x
20 = -1x
(Następna strona)
I. x · z = d
x = d : z
z = d : x
II. b · a = c
b = c : a
a = c : b
III. p · r = w
p = w : r
r = w : p
IV. m · n = z
m = z : n
n = z : m
V. x · y = m
x = m : y
y = m : x
VI. z · y = c
z = c : y
y = c : z
VII. e · f = g
e = g : f
f = g : e
VIII. h · x = y
h = y : x
x = y : h
Pozdrawiam :D